2006
DOI: 10.1103/physrevlett.97.167002
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Polar Kerr Effect Measurements ofSr2RuO4: Evidence for Broken Time-Reversal Symmetry in the Superconducting State

Abstract: Polar Kerr effect in the spin-triplet superconductor Sr2RuO4 was measured with high precision using a Sagnac interferometer with a zero-area Sagnac loop. We observed non-zero Kerr rotations as big as 65 nanorad appearing below Tc in large domains. Our results imply a broken time reversal symmetry state in the superconducting state of Sr2RuO4, similar to 3 He-A.PACS numbers: 74.25. Gz,74.70.Pq,74.25.Ha,78.20.Ls Soon after the discovery of the layered-perovskite superconductor Sr 2 RuO 4 [1], it was predicted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
623
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 594 publications
(657 citation statements)
references
References 26 publications
30
623
4
Order By: Relevance
“…One experiment which directly probes the anomalous ac Hall conductivity considered here is the polar Kerr effect [1]. In this experiment, linearly polarized light beam which is normally incident on the superconducting planes is reflected back as elliptically polarized light.…”
Section: Kerr Effect and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One experiment which directly probes the anomalous ac Hall conductivity considered here is the polar Kerr effect [1]. In this experiment, linearly polarized light beam which is normally incident on the superconducting planes is reflected back as elliptically polarized light.…”
Section: Kerr Effect and Discussionmentioning
confidence: 99%
“…We also uncover some unusual features of the collective modes of a chiral superconductor, namely, that they are not purely longitudinal and couple to external transverse fields. The experiment by Xia et al found a Kerr angle of approximately 60 nanoradians at a frequency, ω ≃ 0.8 eV, which is small compared to the Kerr angle observed in typical ferromagnets, but can be understood qualitatively if one notes that the superconducting gap (or order parameter) for Sr 2 RuO 4 is substantially reduced from that of a typical ferromagnet [1]. The Kerr angle at high frequencies is related to the ac Hall conductivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sr 2 RuO 4 , the only superconducting layered perovskite without Cu, features an odd-parity, spin-triplet, likely chiral p-wave pairing state [1][2][3][4][5]. In addition to an exotic pairing symmetry, unconventional flux states have also been observed in this superconductor.…”
mentioning
confidence: 98%
“…Assuming that superconductivity in this material is two-dimensional in nature, the fourfold tetragonal crystalline symmetry dictates that the pairing symmetry must be one of the five representations 7 . Among those, only the two-component, p x ±ip y state is consistent with the muon spin rotation 8 and Kerr rotation 9 measurements that suggest the presence of a spontaneous magnetic field in the superconducting state of Sr 2 RuO 4 , making it an electronic analogue 7 of the superfluid 3 He A-phase, and a chiral p-wave superconductor for which a Majorana zero-energy mode bound to the normal core of a half-flux quantum vortex has been predicted 1,2 . An important question of interest is what is the microscopic mechanism responsible for such a highly exotic superconducting state.…”
mentioning
confidence: 99%